Educational and psychosocial experiences of the left-behind children of female Indonesian migrant workers in Banten, Indonesia - Sri Nurul Milla (Kulliyyah of Education, International Islamic University Malaysia, 2017)
Millions of Indonesian children are left behind by their mothers who work as migrant workers. The main purpose of this qualitative study is to understand the educational and psychosocial experiences of the left-behind children of female Indonesian migrant workers in Banten, Indonesia. Besides, this study aimed to understand the major challenges experienced by the left-behind children and the coping strategies employed by them in dealing with the absence of their migrated mothers. Semi-structured interviews were conducted with two females and three males left-behind children of female Indonesian migrant workers in Banten, Indonesia. They were between the ages of 15 and 17. Additionally, their available caregivers and school teachers were interviewed in order to triangulate the data. The data were analyzed using thematic analysis and then discussed using the DCR (Describe – Compare – Relate) technique suggested by Bazeley (2009). The result emerged from this study showed that the left-behind children experienced insecure attachment to their mothers. Furthermore, they were suffering from lack of parental engagement in their academic affairs shown in various ways. However, they were reported to have good academic performance. The findings suggested that God-reliance has helped these left-behind children to cope with their maternal absence. A model to understand the educational and psychosocial experiences of the left-behind children of female Indonesian migrant workers is proposed and recommendations were also made for future research to investigate the extent to which maternal migration influences different aspects of the left-behind children's educational outcomes.